A multivocal study to improve the implementation of global requirements change management process: A client‐vendor prospective. Issue 8 (17th February 2020) - Akbar, Muhammad Azeem; Mahmood, Sajjad; Alsanad, Ahmed; Alsanad, Abeer Abdul‐Aziz; Gumaei, Abdu; Qadri, Syed Furqan
Abstract: Software development is a complex task, and the introduction of multi‐site development teams spread across the globe makes it even harder. Requirement changes during the software development process are inevitable, and failing to manage evolving requirements is one of the contributors to project failures. Requirements change management (RCM) becomes difficult in global software development (GSD) projects due to the need to communicate and coordinate between stakeholders in a distributed environment. This research work aims to identify the factors that have positive impacts on RCM activities in GSD. We conducted a multi‐vocal literature review (MLR) and a questionnaire survey study to identify the RCM success factors. The results of the t ‐test (ie, t = 0.0347 and P = .700 > .05) and correlation (rs (25) = 0.573, P = .003) indicates that there is no significant difference between the findings of MLR and the questionnaire survey. The identified factors were further analyzed in the context of client and vendor organizations to better understand the RCM success factors in both types of GSD firms. The findings of this study can provide a useful framework for tackling problems associated with RCM in a GSD environment that is significant to the progression of GSD firms.